2011
DOI: 10.1080/15374416.2011.546048
|View full text |Cite
|
Sign up to set email alerts
|

Negative Cognitive Style Trajectories in the Transition to Adolescence

Abstract: The development of negative cognitive style was examined in a longitudinal study of 366 community youth. Cognitive style and depressive symptoms were evaluated at ages 11, 13, and 15. Latent growth mixture modeling identified three unique trajectory patterns of negative cognitive style. The normative group (71% of the sample) displayed the least negative cognitive style and lowest depression scores at all assessments. The increasing group (22% of the sample) displayed a cognitive style that was comparable to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 5 publications
2
25
2
2
Order By: Relevance
“…Sometimes, these early experiences lead children to accept attitudes and beliefs that will later prove maladaptive” (Beck & Young, 1985, p. 207, as cited in Bruce et al, 2006). The links between negative parenting style and negative youth cognitive style are well supported (e.g., Garber & Flynn, 2001; McKee et al, 2014; Mezulis et al, 2011) as are the links between negative cognitive style and depression (e.g., Jacobs, Reinecke, Gollan, & Kane, 2008). One study that builds upon both attachment and cognitive models, for example, reported that negative attributions fully mediated the association between attachment security and depression (Margolese, Markiewicz, & Doyle, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Sometimes, these early experiences lead children to accept attitudes and beliefs that will later prove maladaptive” (Beck & Young, 1985, p. 207, as cited in Bruce et al, 2006). The links between negative parenting style and negative youth cognitive style are well supported (e.g., Garber & Flynn, 2001; McKee et al, 2014; Mezulis et al, 2011) as are the links between negative cognitive style and depression (e.g., Jacobs, Reinecke, Gollan, & Kane, 2008). One study that builds upon both attachment and cognitive models, for example, reported that negative attributions fully mediated the association between attachment security and depression (Margolese, Markiewicz, & Doyle, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…One recent study found a trend for adolescent girls to report more overgeneral memories than boys (Stange et al 2013a); however, previous research indicated boys reported more overgeneral memories than girls (Heron et al 2012) or found no difference in overgeneral memory retrieval between the sexes (Kuyken and Dalgleish 2011). Although gender differences in other cognitive vulnerabilities to depression have robust support (Charbonneau et al 2009; Hankin et al 1998; Hyde et al 2008; Mezulis et al 2011), gender differences in overgeneral autobiographical memory or in the relationship between overgeneral autobiographical memory and depression have not been established and are deserving of further research (Raes et al 2012; Rawal and Rice 2012). …”
Section: Introductionmentioning
confidence: 99%
“…These developmental differences in depression prevalence are likely due to complex and constantly shifting differences between adolescent and adult populations that cannot be fully addressed by the scope of our work, including pubertal changes in the transition to adulthood (27, 28) and an individual’s negative cognitive style, which demonstrates distinct trajectories across adolescence that are impacted by factors including maternal parenting and cognitive style, biological sex, and temperament (29). Given the roles of high NA and low PA in consolidating risk to depression from adolescence into adulthood, we examined the relationships between trait affect and depressive symptoms among a sample of adolescents and a sample of young adults to (a) compare developmental periods of lower versus higher vulnerability to depressive symptoms and (b) examine whether NA and PA represented distinct constructs from the trait-like qualities of depressive symptoms.…”
Section: Theory On Trait Affect and Depressive Symptomsmentioning
confidence: 99%